Analisa Lama Waktu Penyimpanan CPO Dan Variasi Suhu Terhadap Perubahan Mutu CPO - Ahmad Fikriyadi (Politeknik Sampit, 2023)
A decrease in the quality of CPO can occur during storage and shipping due to an oxidation reaction with oxygen in the air, a hydrolysis reaction. The longer the CPO storage period, the greater the quality degradation that occurs. CPO storage temperatures that are not properly controlled are also often the cause of a decline in CPO quality. CPO quality is indicated by several parameters, namely free fatty acid content, impurities content, and moisture content. CPO has special characteristics that differ from other vegetable oils which affect its handling during storage. The purpose of this research is to determine the optimum temperature and storage time so that the quality of CPO meets the standards. This research was conducted at the company PT. Subur Agro Makmur, located in Bajayau Village, West Daha District, Hulu Sungai Selatan Regency, South Kalimantan Province. This research was conducted by observing several parameters of the CPO storage process, namely storage time and temperature variations including levels of free fatty acids, impurities, and water. The results of this study are the optimum CPO storage temperature for CPO quality, namely 50oC with an increase in free fatty acids of 0.11, impurities content of 0.00075 per three hours and water content closed of 0.0075 per three hours, and the optimum storage time for CPO is 6 hours